INCREASING THE ACTIVITY AND LEARNING OUTCOMES OF IPAS WITH GUIDED INQUIRY LEARNING MODEL MI AL MUBAROK BATURAJA - Ary Forniawan (Jurnal Scientia, 2023)
This study aims to improve the activity and learning outcomes of IPAS with a guided inquiry learning model in class IV MI Al Mubarok Baturaja. The background of this research is the low activity and learning outcomes of IPAS. The research subjects were grade IV students of MI Al Mubarok Baturaja, totaling 19 students. This type of research is Classroom Action Research. The research design used includes the planning stage, action implementation and observation, and reflection. The data collection instruments used were student activity observation sheets, and LKS. The data analysis technique used was descriptive qualitative data analysis. Based on the results of data analysis in cycle I, meeting I student activity showed 68.68% with an average score of 79.9. Meeting II showed 76.66% with an average score of 83.5. After making improvements in cycle I, namely in the aspects of orientation, formulating simple hypotheses, and formulating conclusions, student activity has increased. Based on the results of data analysis in cycle II, meeting I student activity showed 82.6% with an average value of 80.89, meeting II showed 82.8% with an average value of 82.89. The results showed that the guided inquiry method can improve the activity and learning outcomes of IPAS in class IV MI Al Mubarok Baturaja.